Hythlodaeus' Second Marathon Sentence of 926 Words and the "Contextual Launch" of the Utopia - Malsbary, Gerald (Moreana, 2021)
This article is a follow-up to a previous one in Moreana 51 (2014), which provided a detailed analysis of the immediately preceding 464-word sentence. The two sentences placed near the end of Utopia I work together to illustrate the political wisdom (in both domestic and foreign affairs) which the fictional Hythlodaeus has acquired in his travels, and at the same time encourage readers of Utopia to look forward to, and to accept the wisdom of the Utopians way of life as a positive model for Europe. There is an undoubted harmony between the sensible practices of the "Achorians" and "Macarians" and More's political philosophy as revealed in his epigrams. Nevertheless, the two long sentences also function as praeambula to the full-length account of the Utopians, and they are meant to guide our interpretation. The details of their structure, here analyzed, bring about certain rhetorical effects. In a crescendo of irony, the long sentences establish a rather peculiar character for Hythlodaeus as the sole narrator of Utopia II: he is an independent, utterly frank witness to this fictional "reality" of More's creation, and by the end of Utopia I we readers are prepared to listen to Utopia II with very critical ears indee.